Outcome of children with life-threatening asthma necessitating pediatric intensive care - Cheung Kam-Lau; Leung Ting-Fan; Tang Wing-Sum; Hon Kam-Lun; Ng Pak-Cheung (BMC, 2010)
Abstract Objective To report the outcome of children with life-threatening asthma (LTA) admitted to a university Pediatric Intensive Care Unit (PICU). Methods Retrospective study between October 2002 and May 2010 was carried out. Every child with LTA and bronchospasm was included. Results 30 admissions of 28 patients (13 M, 17 F) were identified which accounted for 3% of total PICU admissions (n = 1033) over the study period. The majority of patients were toddlers (median age 3.1 years). Few had past history of prematurity, lung diseases, or neuro-developmental conditions. Approximately half had previous admissions for asthma and one-forth with history of non-compliance to recommended treatment for asthma. One patient had parainfluenza virus and one had rhinovirus isolated. None of these factors were associated with need for mechanical ventilation (n = 6 admissions). Comparing with patients who did not receive mechanical ventilation, ventilated children had significantly higher PIM2 score (1.65 versus 0.4, p < 0.001), higher PCO2 levels (9.3 kPa versus 5.1 kPa, p = 0.01) and longer PICU stay (median 2.5 days versus 2 days, p = 0.03) The majority of patients received systemic corticosteroids, intravenous or inhaled bronchodilators. There was one pneumothorax but no death in this series. Conclusions LTA accounted for a small percentage of PICU admissions. Previous hospital admissions for asthma and history of non-compliance were common. Approximately one quarters required ventilatory supports. Regardless of the need for mechanical ventilation, all patients survived with prompt treatment.